A Study of Grain Yield Stability and Relations among Some Agronomic Traits in Durum Wheat Genotypes - M. M. Shariftabar (Tulīd va Farāvarī-i Maḥṣūlāt-i Zirā̒ī va Bāghī, 2015)
In order to determine grain yield stability and yield components in durum wheat, 49 genotypes from International Durum Yield Nursery (IDYN), received from International Research Center for Maize and Wheat Improvement (CIMMYT) with one cultivar as check, were studied in an alpha lattice design with two replications at five locations including Karaj, Darab, Neishabour, Khorramabd and Gonbad. Grain yield stability analysis with AMMI and SHMM models revealed that four genotypes including 3, 10, 11 and 25 lines were more stable genotypes in this study. Based on AMMI model, Karaj station with high and negative loading of the first principal component and Khorramabad with high and positive loading of the first principal component, PCA1, did not display adaptability with any genotypes in this study. SHMM model revealed that the pattern of genotype clustering was a function of stability and adaptability of genotypes in the study locations. Path analysis revealed that the direct effect of biomass and harvest index on grain yield was high and significant. Among yield components, the number of spike per square meter showed high and positive direct effect on grain yield.